An Approach To Media Multiplexity In Superior-Subordinate Relations In Government Institutions - Mutia Susana (PERSPEKTIF, 2023)
This paper aims to show how the use of multiple media (multimodality) has an effect on increasing the closeness of relationships. The problems are focused on improving relationships that are usually "equal" such as partners, friends, family, allowed to be applied in "unequal" relationships, such as superiors and subordinates. In order to approach this problem, a theoretical reference from Hyaronthwaite's Media Multiplexity Theory (MMT is used which states that the more use of media creates close relationships and the weaker the relationship we have with someone, the less media we use to interact with that person. This research was analyzed interpretively by interviewing employees at the Ministry of PUPR. The data is collected through in-depth interviews and analyzed qualitatively by clustering 3 things to be observed, which is relationship ties, hierarchy of media use in the institution studied, convenience and motivation from using multiple media. This study concludes that generational differences and motivation for using media affect the formation of strong bonds between superiors and subordinates that influenced by the motivation for using social media, which is to be appreciated by superiors. On the other hand, social media in "unequal" relationships is used only a complement to communication. In addition, culture and digital work processes also affect the convenience of media users.